IDENTIFIKASI SELF DISCLOSURE SISWA TERHADAP GURU BIMBINGAN DAN KONSELING DI SMP N 7 KOTA JAMBI - Mona, Mona; Rasimin, Rasimin; Yusra, Affan (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The development and life process of each student is very likely to encounter various problems. Each issue will likely impact students. Through self-disclosure, students can express their feelings, opinions and problems to other people. At school, guidance and counseling teachers have a role in helping and alleviating problems experienced by students. This research aims to see students' self-disclosure towards guidance and counseling teachers at SMP N 7 Jambi City. This research uses quantitative descriptive methods. In this research, it was found that 60 students were open to their guidance and counseling teachers who were also respondents in the research. The results of the research show that students' self-openness towards guidance and counseling teachers at SMP N 7 Jambi City as a whole is at a percentage of 61.84% which is included in the majority proportion category.